Knowledge, attitudes and practices related to dietary salt intake among adults in North India. Issue 9 (28th December 2018) - Garg, Vandana; Shivashankar, Roopa; Kondal, Dimple; Ghosh, Shreeparna; Khandelwal, Shweta; Gupta, Ruby; Krishnan, Anand; Amarchand, Ritvik; Prabhakaran, Dorairaj; Mohan, Sailesh
Abstract: Objective: To assess the knowledge, attitudes and practices related to salt consumption among adults in rural and urban North India. Design: Data for the study were obtained from a community-based cross-sectional survey using an interviewer-administered questionnaire and 24 h urine samples. Setting: Data collection was conducted during March–October 2012 in rural Haryana and urban Delhi in North India. Participants: Adults ( n 1635) aged ≥20 years (701 in rural Haryana; 934 in urban Delhi). Results: Twenty-four per cent of rural and 40·5 % of urban participants knew that a high-salt diet causes high blood pressure. Nearly one-fifth of both rural and urban participants knew that there should be a maximum daily limit for consumption of salt. In rural and urban areas, 46·6 and 45·1 %, respectively, perceived it important to reduce the salt content of their diet; however, only 3·7 and 10·2 %, respectively, reported taking some actions. Participants reported they were consuming 'too little salt', 'just the right amount of salt' or 'too much salt', but their corresponding mean (95 % CI) actual salt consumption (g/d; as measured by 24 h urinary Na excretion) was higher, especially among rural participants (rural: 9·2 (8·13, 10·22), 8·5 (8·19, 8·77) or 8·4 (7·72, 8·99); urban: 5·6 (4·67, 6·57), 5·7 (5·32, 6·01) or 4·6 (4·10, 5·14), respectively). Conclusions: Knowledge about the deleterious health impact of excess salt consumption is low in this population. Tailored public education for salt reduction is warranted with a particular focus on rural residents.